Artificial Intelligence Development on “Golem” Non-Playable Character in Miner Quest Games With Finite State Machine Method - Zikri, Afdhal (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2024)
Digital educative game is an example of technology currently often used by kindergarten teachers to make topics or subjects easier for students to understand. By using the function of digital educational games, researchers plan to develop a "mining tour" game, with the objective that this game can convey knowledge or information about mining materials to early childhood. This game has obstacles that must be overcome or defeated, has a strong boss or monster at the end of each level and focuses on training to get mining results. This game was developed using the finite state machine method for non-playable characters (NPC). This method focuses on the player's choices when completing each mission in the game. In general, the appearance of this game uses references from Mario Bros. 2 game, and the quest to get many mining products (coal and nickel). The results of this study aim to determine how effective the "Miner" game is for kindergarten. Through live testing, we can evaluate the success of the "mining" game using the mined materials and develop the NPC system generated through the finite machine method.